Horizontal Differentiation Matters: Moderating Influence of the Type of Upper Secondary Education on Students' Transitions. Issue 1 (2nd January 2019) - Boyadjieva, Pepka; Ilieva-Trichkova, Petya
Abstract : This article explores how the horizontal differentiation of upper secondary education affects students' transitions after graduation. It builds upon the institutional perspective on education and draws on data from a nationally representative survey. The analysis shows a considerable variation in graduates' patterns of transition according to the type of secondary education and that the type of secondary education program moderates the effect of the academic achievement and of students' socioeconomic background on students' patterns of transition.